Integrative stress management for global workforce: music-based and exercise intervention for overseas employees - Wei, Yaming; Wu, Huijuan; Song, Yongfan (Frontiers in Public Health, 2025)
BackgroundOverseas employees experience high stress from cultural, work, and social challenges. This study examines whether combining music-based intervention and aerobic exercise reduces stress, and explores the influence of age, occupation, music preference, and long-term effects.MethodsWe conducted a randomized trial with 92 Chinese expatriate workers, randomly assigned to either (1) an experimental group receiving weekly 45-min resource-oriented music-based intervention sessions plus 30-min moderate-intensity exercise, or (2) a control group receiving placebo interventions (background music + stretching) for 5 weeks. Stress levels were assessed using the Global Assessment of Recent Stress (GARS) at baseline (pre-intervention), post-intervention (0 months), and at 1-, 3-, and 6-month follow-ups through online surveys, supplemented by qualitative interviews.ResultsThe experimental group demonstrated significant stress reduction (GARS scores decreased from 3.59 ± 0.71 to 2.68 ± 0.57, p < 0.001), with effects sustained at 6 months (p < 0.05). Subgroup analyses showed enhanced efficacy for (a) employees aged 40–49 years, (b) classical music listeners, and (c) high-stress occupations like seafarers. Qualitative data corroborated these findings by highlighting participants’ subjective experiences of improved emotional regulation, reduced anxiety, and increased relaxation, aligning closely with the quantitative stress reduction outcomes.ConclusionThis dual-modality intervention effectively reduces stress among overseas workers, with benefits influenced by individual characteristics. The results support implementing personalized, non-pharmacological stress management programs in multinational corporations to promote global workforce mental health.